Integrasi Ibadah dan Kesehatan Mental dalam Perspektif Psikologi Agama Islam - Yunita Sari; Miftahul Jannah; Salami Mahmud (Journal of Innovative and Creativity, 2026)
The growing prevalence of mental health issues in the digital era reflects a deepening spiritual void among modern individuals, especially younger generations. This study aims to analyze the relationship between Islamic worship and mental health from the perspective of modern Islamic psychology of religion. Using a qualitative descriptive approach through library research, data were collected from the Qur’an, Hadith, classical Islamic texts, and contemporary studies on psychology of religion and mental health. The findings indicate that acts of worship particularly prayer (shalat), remembrance (dhikr), and fasting (sawm) play a therapeutic role in maintaining psychological balance by regulating emotions, nurturing life meaning, and strengthening spiritual resilience. The holistic view of the unity of body, intellect, and soul found in classical Islamic thought remains consistent with modern theories such as Pargament’s religious coping and Frankl’s logotherapy. The study also highlights the importance of family, education, and spiritual communities as protective factors for digital generations vulnerable to stress and existential anxiety. Therefore, integrating Islamic worship values within the framework of modern psychology of religion offers both conceptual and practical solutions for enhancing mental health in contemporary society. Fenomena meningkatnya gangguan kesehatan mental di era digital menunjukkan adanya kekeringan spiritual yang dialami manusia modern, terutama di kalangan generasi muda. Penelitian ini bertujuan untuk menganalisis hubungan antara ibadah dan kesehatan mental dalam perspektif psikologi agama Islam modern. Menggunakan metode kualitatif dengan pendekatan studi kepustakaan, data diperoleh dari Al-Qur’an, hadis, literatur klasik Islam, serta kajian kontemporer mengenai psikologi agama dan kesehatan mental. Hasil penelitian menunjukkan bahwa ibadah terutama shalat, dzikir, dan puasa memiliki fungsi terapeutik yang nyata terhadap keseimbangan psikologis. Ibadah berperan dalam regulasi emosi, pembentukan makna hidup, dan penguatan resiliensi spiritual. Konsep kesatuan jasad, akal, dan jiwa yang diperkenalkan oleh pemikir Islam klasik tetap relevan dengan teori religious coping (Pargament) dan logoterapi (Frankl). Selain itu, penelitian ini menyoroti pentingnya pendidikan dan komunitas spiritual sebagai benteng mental bagi generasi digital yang rentan terhadap stres dan kehilangan arah hidup. Dengan demikian, integrasi nilai-nilai ibadah dalam kerangka psikologi agama Islam menjadi solusi konseptual dan praktis dalam membangun kesehatan mental manusia modern.